Day 2 Tue, October 10, 2017 2017
DOI: 10.2118/187364-ms
|View full text |Cite
|
Sign up to set email alerts
|

Further Insights into the Mechanism of Disproportionate Permeability Reduction

Abstract: Disproportionate permeability reduction (DPR) is a phenomenon whereby many water-soluble polymer solution and polymer gels reduce the permeability to water flow more than to oil or gas flow. DPR is important for some gels that are applied to production wells in water-shutoff treatments. The mechanisms of DPR need more investigation and clarification. In this study, experiments on two different scales, core- and micro-model-scale, were conducted to study the mechanism of DPR in flow through permeable medium tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…Zhang et al (2016) suggest that as gas saturation decreases, the potential of the gel to limit water relative permeability sharply decreases. 77 Moreover, recent investigations 33,35,36,78,79 state that significant trapping of residual nonwetting saturation due to RPM treatment results in a greater restriction to water (wetting) flow and eventually significantly increases Frr w Considering all above, we conclude that the reduction in Frr w with increasing water flow rates is due to both the deformation of the gel layer and decreasing S gr .…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Zhang et al (2016) suggest that as gas saturation decreases, the potential of the gel to limit water relative permeability sharply decreases. 77 Moreover, recent investigations 33,35,36,78,79 state that significant trapping of residual nonwetting saturation due to RPM treatment results in a greater restriction to water (wetting) flow and eventually significantly increases Frr w Considering all above, we conclude that the reduction in Frr w with increasing water flow rates is due to both the deformation of the gel layer and decreasing S gr .…”
Section: Resultsmentioning
confidence: 54%
“…These observations are considerably different from those reported previously, where the gel formed only in the edges and crevices of grains. 23,31,35 Most likely, in these previous studies, gel layer formation was not observed as the layer was too thin and totally transparent (but still existed, see above).…”
Section: Effect Of Irreducible Water Saturation (S Wir )mentioning
confidence: 87%
See 2 more Smart Citations
“…24,41,44,152,153,157 Similarly, these roles would reverse if the pore surface was oil/ gas wet. 24,44 Elsewhere in the literature, this mechanism is referred to as segregated pathways, 24,28,29,44,46,152,153,157,162,163 fl u i d p a r t i t i o n i n g , 4 1 , 1 6 0 a n d fl u i d d i s t r i b ution. 22,23,110,111,119,151,164 For consistency, the term "fluid segregated pathways" is used in this review.…”
Section: Polymer Adsorptionmentioning
confidence: 99%